Hazardous and Toxic Waste Management Analysis at UNS Hostpital Indonesia - Hashfi Hawali Abdul Matin; Ardhitya Rio Febrian; Aini Mar’atush Sholekha; Asih Kinanthi; Frista Ananda Rizky; Berlian Warit Amalia; Damayanti Miftachus Sholichah; Yhagie Titis Wis Dhinanti (Waste Technology, 2021)
National development is increasing every year driven by infrastructure development in all fields including hospitals. Hospitals and health care facilities produce B3 waste that enters the environment through soil, water, air, and biota media. The UNS Hospital is a hospital with service types A, B, and C located in Kartasura District, Sukoharjo Regency, Central Java, Indonesia. The method used in this study observation and interviews. The data collected is for B3 waste management which includes reduction and sorting, storage, transportation, and processing. The data obtained were than analyzed descriptively and compared with Permenkes No. 7 of 2019 regarding hospital environmental health and Government Regulation No. 22 of 2021 regarding environment management. Basically, there are 2 types of waste generated by UNS Hospital, namely medical and non-medical. Currently, UNS Hospital distinguishes waste into 2 types, namely Covid and Non-Covid. There are 6 stages of waste management in UNS Hospital, namely as follows. Sorting is carried out in each ward or treatment room by sorting waste according to its type. Waste packaging, safety box provided. The collection is by sorting the waste put into the trash and then transported by Cleaning Service in a special trolley and collected at the TPS. Storage of medical waste 1-2 days while non-medical 1 year. The transportation and processing of waste is carried out by a third party. Hazardous and toxic waste is one of the materials that requires special handling. The agency that will handle B3 waste must have permit or certification related to the management carried out. UNS Hospital is a health care agency that participates in producing B3 waste with good waste management according to existing regulations.